Anastrepha fruit flies (Diptera; Tephritidae) in Costa Rica: four new records - Soto-Manitiu, Julia (1988)
Here we report the results of sampling mango (Mangifera indica L.) orchards (May 1985-July 1986) for fruit flies in three localities (Cañas, prov. Guanacaste; Lepanto, prov. Puntarenas and Orotina, prov. Alajuela)